Effect of Relaxation Benson Technique on Nausea and Vomiting among Primigravida: Effect of Relaxation Benson Technique on Nausea and Vomiting among Primigravida (Journal of Hama University, 2025)
Introduction- Three-quarters of pregnant women suffer from nausea and vomiting, and although it is a non-life-threatening problem, it can be stressful for both pregnant women and their families, and it can have a negative impact on their sense of well-being and the quality of their daily life, preventing them from enjoying the privacy of pregnancy.The aim- of the current study was to investigate the effect of Benson's relaxation technique on nausea and vomiting among primigravida pregnant women.Research material and methods: A quasi-experimental study was conducted on a purposive sample of 60 primiparous pregnant women from the outpatient gynecology clinic at the Maternity and Children's Hospital and the health center in the eighth project in Lattakia city. Data were collected during the period from 28-8-2023 to 25-2-2024 using the demographic and health data form and Modified 24-hour Pregnancy- Unique Quantification of Emesis (PUQE) QuestionnaireResults- The results of the study showed that the degree of nausea and vomiting after applying the Benson relaxation technique became mild in the highest percentage of pregnant women in the experimental group 66.7%, in contrast, it was moderate in about three-quarters of pregnant women in the control group 73.3%, and the differences between the two groups were statistically significant.Conclusion and recommendations: The Benson relaxation technique is effective in managing nausea and vomiting in primiparous pregnant women; therefore, it is recommended to integrate it into the management of nausea and vomiting during pregnancy in health centers and women's clinics in maternity hospitals.
Keywords: Benson technique, relaxation technique, nausea, vomiting, primiparous pregnant women.